Influence of IL-10, IL-6 and TNF-α gene polymorphism on obesity: IL-10, IL-6 and TNF-α polymorphism and obesity - Hasan Azeez, Sarhang (Cellular and Molecular Biology, 2023)
Obesity is one of the most serious public health issues. Obesity is caused by a complex interaction of genetic, metabolic, social, cultural, and environmental variables. Obesity prevalence in both children and adults has risen substantially in recent years, and the condition is now considered an epidemic. Forty-two obese males with BMI≥ 30 were included in this study. Their age interval was (16-45) years. Controls include 42 males with normal BMI≤25 and age group (16-45) years were selected. Serum level and single nucleotide polymorphism were determined for IL-10, IL-6 and TNF-α. For evaluating gene polymorphism, the allele was counted by direct allele counting. The Hardy–Weinberg equilibrium was assessed with the χ2-test. In IL-10 the GA genotype was found about 5th folded than controls with (OR:4.71, C.I:1.86 to 11.91). IL-6 genotype GG was revealed as an etiologic factor and GC as a protective factor for obesity. While for TNF-α the GG genotype was protective and GA was a risk factor for obesity. Point mutation in G/A for IL-10 and TNF-α were considered as developing factors, whereas the GG genotype was etiologic to obesity in this study.